ANALYSIS CORRELATION SUPPORT HUSBAND WITH PARTICIPATION OF MOTHERS IN PREGNANT WOMEN'S CLASSES IN THE WORK AREA VILLAGE HEALTH POST KALIPARE MALANG REGENCY - Dina Beti Isnovita; Anik Sri Purwanti (Journal of Public Health Science, 2026)
Pregnancy is a physiological process that requires attention special Because can accompanied by various risk dangerous complications​ Mother and fetus . One of the effort improvement health Mother pregnant is through class Mother pregnancy with the aim of increase knowledge , readiness childbirth , as well as detection early complications pregnancy . However , participation Mother in class Mother pregnant Still not optimal. One of the influencing factors​ participation Mother is support husband . Research This aim For analyze correlation support husband with participation Mother in class Mother pregnant in the work area Village Health Post Kalipare Malang Regency . Research This use design quantitative with cross-sectional approach . Population in study This is all over Mother pregnant in the work area Village Health Post Kalipare Malang Regency with amount sample A total of 30 respondents were taken use purposive sampling technique . Data collection using questionnaire support husband and sheet observation participation class Mother pregnant . Data analysis used the Spearman Rank test. The results of the study show part big respondents get support husband category sufficient (43.3%) and some big Mother No active follow class Mother pregnant (60.0%). The Spearman Rank test results obtained p- value <0.001 with a correlation coefficient of 0.710 which indicates there is connection strong between support husband with participation Mother in class Mother pregnant . Support husband play a role important in increase participation Mother follow class Mother pregnant